(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
The purpose of this study was to determine the role of sense of humor and work stress among high school teachers in Sumbawa Besar. This research used a quantitative correlational design. The study population comprised 147 teachers, and a sample of 103 respondents was obtained using a purposive sampling technique. The research instrument consisted of a sense-of-humor scale and a work-stress scale. The validity results showed that the sense of humor scale had 18 valid items out of 24, with validity coefficients ranging from 0.312 to 0.721 and a reliability of α = 0.871. The work stress scale had 21 valid items out of 35, with validity coefficients ranging from 0.301 to 0.746 and a reliability of α = 0.903. Data analysis used descriptive statistics, and Pearson Product-Moment correlation was tested to examine the relationship between research variables. The results showed a significant negative relationship between sense of humor and work stress, with r = -0.570 and p = 0.000 (p < 0.05). The stronger a teacher’s sense of humor, the lower their work stress. This finding supports the importance of developing a sense of humor in reducing teacher work stress, although the study was limited to high school teachers in Sumbawa Regency.